2009
DOI: 10.1021/pr800887u
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Detergent-Solubilized Membrane Proteins from Insect-Developmental Forms of Trypanosoma cruzi

Abstract: The cell surface of Trypanosoma cruzi, the etiologic agent of Chagas disease, is covered by a dense layer of glycosylphosphatidylinositol (GPI)-anchored molecules. These molecules are involved in a variety of interactions between this parasite and its mammalian and insect hosts. Here, using the neutral detergent Triton X-114, we obtained fractions rich in GPI-anchored and other membrane proteins from insect developmental stages of T. cruzi. These fractions were analyzed by twodimensional liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 59 publications
3
56
2
1
Order By: Relevance
“…On the other hand, 5 TcTASV-A genes were identified in the trypomastigote proteome, in agreement to our evidences of the intracellular localization of TcTASV-A in trypomastigotes (unpublished observations). The proteomes of metacyclic trypomastigotes and epimastigotes –designed to preferentially identify membrane-bound and/or hydrophobic proteins- failed to find any TcTASV peptide [64], in line with results presented here that showed a minimum expression (or absence) of TcTASV-C in insect-derived parasite-stages.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, 5 TcTASV-A genes were identified in the trypomastigote proteome, in agreement to our evidences of the intracellular localization of TcTASV-A in trypomastigotes (unpublished observations). The proteomes of metacyclic trypomastigotes and epimastigotes –designed to preferentially identify membrane-bound and/or hydrophobic proteins- failed to find any TcTASV peptide [64], in line with results presented here that showed a minimum expression (or absence) of TcTASV-C in insect-derived parasite-stages.…”
Section: Discussionsupporting
confidence: 86%
“…This could be due to the translocation of cytoplasmic calpains to the plasma membrane after cellular stimulation. Ennes-Vidal et al (2011) showed by ultrastructural immunolabeling that calcium-dependent cysteine peptidases are mainly located at the cytoplasm of epimastigotes [50].Recently, we identified seven calpain-like proteins including two cytoskeletal associated proteins CAP5.5 in the plasma membrane of T. cruzi epimastigotes and metacyclic trypomastigotes [51]. Six of these calpain-like proteins contain N-terminal fatty acid acylation motifs, indicating an association with cellular membranes.…”
Section: Resultsmentioning
confidence: 79%
“…Purification of GPI-anchored Proteins-Pellets containing 1.5 ϫ 10 8 parasites were homogenized in 2 ml of GPI buffer (10 mM Tris-HCl, pH 7.4, 150 mM NaCl, 2% Triton X-114 (TX-114), 1 mM PMSF and a protease inhibitor mixture (Sigma)) on ice for 1 h and the homogenate processed as described (37). Briefly, the homogenate was centrifuged at 8,800 ϫ g for 10 min at 0°C, and the supernatant (S1) was stored at Ϫ20°C for 24 h. The pellet (P1) was washed with 1 ml of buffer A (10 mM TrisHCl, pH 7.4, 150 mM NaCl, 0.06% TX-114, 1 mM PMSF), sonicated, and resuspended in denaturing loading buffer containing 6 M urea.…”
Section: Methodsmentioning
confidence: 99%